IMPLEMENTATION OF (XP, YP) REPRESENTATION TO AWGNI STRUCTURAL TYPE SENTENCES - Berhanu Asaye Agajie (LITERA, 2020)
The objective of this study was designed to implement {XP, YP} representations in an attempt to examine Awgni structural type sentences. A descriptive study design and purposive sampling technique were used to look at the proposed research objective. Tools used throughout collecting data were interview and focused group discussion. The research finding showed that simple sentence structures of Awgni have no more than one Verbal head. Alternatively, simple, complex, compound, and compound complex sentence may perhaps contain two and more verbal heads in their hierarchical structures. Sentences regarding their perceptible emergence, structure, syntactic representations they comprise were distinct. Accordingly, all sentential structures encompass phrasal categories that contain: Determiner Phrase (DP), Prepositional phrase (PP), Noun Phrase (NP), Adverb Phrase (ADVP), Verb Phrase (VP) and Adjective Phrase (AP). Further research is recommending on how Labeling Algorithm {XP, H} and {X, Y} applies to test out Syntactic Object representations found within simple, compound, complex and compound complex sentences of Awgni.Keywords: Awgni, Labeling Algorithm, sentence, structure, syntaxPENERAPAN REPRESENTASI (XP, YP) KEPADA KALIMAT JENIS STRUKTUR AWGNIAbstrakTujuan dari penelitian ini dirancang untuk mengimplementasikan representasi {XP, YP} untuk menguji kalimat tipe struktural Awgni. Desain penelitian deskriptif dan teknik purposive sampling digunakan untuk melihat tujuan penelitian yang diajukan. Alat yang digunakan selama pengumpulan data adalah wawancara dan diskusi kelompok terfokus. Hasil penelitian menunjukkan bahwa struktur kalimat sederhana Awgni tidak lebih dari satu kepala Verbal. Atau, kalimat sederhana, kompleks, majemuk, dan majemuk mungkin berisi dua atau lebih kepala verbal dalam struktur hierarkisnya. Kalimat-kalimat mengenai kemunculan, struktur, representasi sintaksis mereka yang terlihat tidak sesuai. Dengan demikian, semua struktur sentensial mencakup kategori frasa yang berisi: Determiner Phrase (DP), Prepositional Frase (PP), Noun Phrase (NP), Adverb Phrase (ADVP), Verb Phrase (VP) dan Adjective Phrase (AP). Penelitian lebih lanjut merekomendasikan tentang bagaimana Labeling Algorithm {XP, H} dan {X, Y} berlaku untuk menguji representasi Objek Sintaksis yang ditemukan dalam kalimat sederhana, majemuk, kompleks dan kompleks majemuk dari Awgni.Kata kunci: Awgni, label algoritma, objek sintakis, kalimat